Effects of hormone replacement therapy with vitamin C and E supplementation on plasma thyroid hormone levels in postmenopausal women with Type 2 diabetes - Naziroglu, Mustafa; Simsek, Mehmet (Elsevier France-Editions Scientifiques Medicales Elsevier, 2009)
Recent studies have shown that hormone replacement therapy (HRT) can exert regulatory affects on lipid and glucose homeostasis. It has been demonstrated that hyperglycemia also involving the formation of lipid peroxides, exert several biological effects that may contribute to the onset and progression of thyroid and kidney abnormalities of postmenopausal women Type 2 diabetes. Therefore, the aim of our study was to evaluate the effect of HRT, vitamin C and E (VCE) treatments on some plasma biochemical and hematological parameters and plasma thyroid hormone levels in postmenopausal women with or without diabetes. Oral HRT and VCE supplementation were compared with no HRT treatment in 40 non-diabetic postmenopausal women and 40 postmenopausal women with Type 2 diabetes mellitus, in a 6-week randomized prospective study. In the 20 women with diabetes who received oral HRT and the 20 women with diabetes who received HRT plus VCE, there was a significant fall in urea, uric acid, creatinine, total bilirubin, conjugated bilirubin, AST, ALT, LDH values. There was no significant change in red blood cell counts, total protein, albumin, sodium, potassium, hematocrit, hemoglobin and free thyrotoxine and triiodothyronine values in postmenopausal women with diabetes or treated with oral HRT and VCE. In conclusion, daily VCE and HRT administrations seem to produce significant improvement on biochemical parameters in the blood of postmenopausal women with Type 2 diabetes. The HRT and VCE supplementations may strengthen the antioxidant defense system and they may play a role in preventing kidney and liver diseases of postmenopausal women with Type 2 diabetes. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: Oxidative stress; Menopause; Thyroid hormones; Biochemical and hematological values; Vitamin C and E